1997
DOI: 10.1094/pdis.1997.81.10.1196
|View full text |Cite
|
Sign up to set email alerts
|

A Survey for Strains of Xylella fastidiosa in Citrus Affected by Citrus Variegated Chlorosis and Citrus Blight in Brazil

Abstract: Polymerase chain reaction amplification of DNA from various strains of Xylella fastidiosa with tRNA consensus primers produced three different fingerprint groups. The citrus variegated chlorosis (CVC) and mulberry leaf scorch strains were unique and readily separated from each other and all other strains tested. Internal primers were designed based on the sequence of a DNA fragment unique to the CVC strain. An assay was developed with a mixture of these primers and those reported to detect 18 strains of X. fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
0
12
0
4
Order By: Relevance
“…Chemometric analysis showed that the deficiency of P and K in symptomatic trees for all orchards and high concentrations of Fe, Mn and Zn were present in chlorotic areas, although other studies revealed deficiency of zinc in leaves (Beretta et al, 1997). According to the analysis, the deficiency of P and K in symptomatic trees for all orchards and high concentrations of Fe, Mn and Zn present in chlorotic areas of symptomatic trees, may or may not be influenced by the causal agent.…”
Section: Resultsmentioning
confidence: 79%
“…Chemometric analysis showed that the deficiency of P and K in symptomatic trees for all orchards and high concentrations of Fe, Mn and Zn were present in chlorotic areas, although other studies revealed deficiency of zinc in leaves (Beretta et al, 1997). According to the analysis, the deficiency of P and K in symptomatic trees for all orchards and high concentrations of Fe, Mn and Zn present in chlorotic areas of symptomatic trees, may or may not be influenced by the causal agent.…”
Section: Resultsmentioning
confidence: 79%
“…Three additional plants were healthy. The bacterial presence was confirmed before and after the measurements through the polymerase chain reaction (PCR), specific for X. fastidiosa (Beretta et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…The identity of the X. fastidiosa colonies was confirmed based on colony morphology and growth pattern. In addition, samples of single colonies were tested by PCR, using specific primers (1,21), and by ELISA with polyclonal antiserum against X. fastidiosa of citrus (SANOFI; Diagnostics Pasteur S.A., France). All colony samples visually identified as X. fastidiosa were positive in these tests.…”
Section: Methodsmentioning
confidence: 99%
“…Since X. fastidiosa was first shown to cause CVC (3,20), serological (5) and molecular methods (1,21,25) have been developed to detect the bacterium in citrus. The pathogen is naturally transmitted to citrus by sharpshooter (Cicadellinae) leafhoppers (29).…”
mentioning
confidence: 99%